Red flag on the white reporter: a versatile insulator abuts the white gene in Drosophila and is omnipresent in mini-white constructs. - Chetverina, D.; Savitskaya, E.; Maksimenko, O.; Melnikova, L.; Zaytseva, O.; Parshikov, A.; Galkin, A.V.; Georgiev, P. (Nucleic Acids Research, 2008)
Much of the research on insulators in Drosophila has been done with transgenic constructs using the white gene (mini-white) as reporter. Hereby we report that the sequence between the white and CG32795 genes in Drosophila melanogaster contains an insulator of a novel kind. Its functional core is within a 368 bp segment almost contiguous to the white 3'UTR, hence we name it as Wari (white-abutting resident insulator). Though Wari contains no binding sites for known insulator proteins and does not require Su(Hw) or Mod(mdg4) for its activity, it can equally well interact with another copy of Wari and with unrelated Su(Hw)-dependent insulators, gypsy or 1A2. In its natural downstream position, Wari reinforces enhancer blocking by any of the three insulators placed between the enhancer and the promoter; again, Wari-Wari, Wari-gypsy or 1A2-Wari pairing results in mutual neutralization (insulator bypass) when they precede the promoter. The distressing issue is that this element hides in all mini-white constructs employed worldwide to study various insulators and other regulatory elements as well as long-range genomic interactions, and its versatile effects could have seriously influenced the results and conclusions of many works.